Development and face validity of the Danish STOB screening tool for early detection of binge eating disorder in children and adolescents - Sidsel Maigaard; Pernille Andreassen; Loa Clausen; Jens Meldgaard Bruun (Journal of Eating Disorders)
Abstract Background Binge Eating Disorder (BED) is prevalent among children and adolescents and is associated with severe psychological and somatic health complications. Early detection and intervention are therefore crucial. This study aimed to develop, pilot test, and validate the STOB screening tool (Screening Tool for the early detection Of BED), designed for use in children and adolescents aged 13–18 in primary care settings using a qualitative face validity approach. Additionally, the study explored the perceived acceptability of a supplementary dialogue tool. Methods The development, pilot testing, and validation of the screening tool followed a two-phase qualitative process. In phase one, development and pilot-testing of the 6-item STOB tool was conducted. In phase two, the validation process incorporated a survey and semi-structured interviews, both assessing various aspects of the screening tool, including language complexity, usability, acceptability, and the presence of uncomfortable or intrusive terms. A total of 42 participants, aged 14–18 years (mean age = 16.4 years), were recruited from a community sample for the survey (23 females, 19 males). For the interviews, 10 participants (8 females, 2 males; mean age = 15.7 years) from the community sample were included, resulting in seven individual interviews and one group interview. Additionally, two female participants with BED, aged 16 and 17, were recruited for interviews only. Results A total of 16.7% of survey respondents met the screening tool threshold for possible BED, and 4.8% of the total sample scored positive on all questions, further increasing the suspicion of BED. Both the survey and interviews indicated that the screening questions were generally well-understood. However, a few linguistic challenges were identified during interviews, prompting minor semantic adjustments to enhance clarity and accessibility. The Interviews revealed age-related differences in language perception and notable differences in content comprehension between participants with and without BED. Conclusion The STOB screening tool demonstrates acceptable face validity and potential for implementation in primary care, particularly when accompanied by the supplementary dialogue tool. This study underscores the importance of evaluating self-report questionnaires in terms of terminology and acceptability within the target population. Further validation is recommended across broader adolescent populations. Trial registration Not applicable.